Effect of Organic Manures and Biofertilizers on Growth, Yield and Quality of Pea (Pisum sativum L.) - Kumari, Santosh; Kumari, Ranjana; Kumar, Anil (International Journal of Bio-resource and Stress Management, 2022)
The present study was carried out at the Experimental Farm of College of Horticulture and Forestry, Neri, Hamirpur (HP) during November, 2020 to March, 2021. Experiment was laid out in Randomized Complete Block Design with three replications at spacing of 60×10 cm in a plot size of 1.8×1.0 m accommodating 30 plants in each plot. The experiment comprised of seventeen treatment combinations of organic manures and biofertilizers.The results revealed that treatment combination of Rhizobium+PSB+FYM was best for most of the characters like days to marketable maturity (95.00 days), plant height (77.66 cm), number of root nodules plant-1(27.66), number of primary branches plant-1(13.40), number of pods plant-1(23.13), pod length (8.43 cm), pod weight (7.78 g), number of seeds pod-1 (8.13), pod yield plant-1 (97.06 g), pod yield plot-1 (2.90 kg), harvest duration (27.66 days), shelling percentage (50.16%) and protein content (11.62%) followed by RDF and combination of Rhizobium+PSB+Vermicompost. The highest gross income (` 2,57,760 ha-1), net income (` 1,76,720 ha-1) and benefit: cost ratio (2.18) were recorded by the treatment combination of Rhizobium+PSB+FYM. Hence, biofertilizers viz., Rhizobium and PSB when applied along with FYM in pea cultivation, they enhance the growth, yield and quality of the produce.